Tourism Branding as Government Support to Increase Economic Country: Social Network Analysis - Elviria, Samia; Zaki, M.; Suhendri, Suhendri (Publik : (Jurnal Ilmu Administrasi), 2023)
The Indonesian Government seeks to invest in digital communications to strengthen Indonesia's tourism industry and position it as a leading tourist destination. Social media enables organizations to provide personalized and engaging information to communities or individuals efficiently and effectively. Therefore, this study aims to discover how the Indonesian government uses social media (Twitter) to create images that can help boost tourism and the economy after COVID-19. This study uses social network analysis to explain information distribution and interaction. This study analyzes social media networks for promoting and branding Indonesian tourism using a qualitative descriptive and theoretical approach. To visualize data analysis, the Nvivo 12 Plus software, specifically the Twitter Sociogram and Netlytics dataset tools, highlights the results of Social Network Analysis regarding interactions using the hashtag #WonderfulIndonesia. According to the study's findings, the Indonesian government uses Twitter as a means of communication and promotion to improve tourism's image or branding, which is likely to be effective. By mentioning the #WonderfulIndonesia hashtag, government accounts promote tourism branding by disseminating information to the public, private sector, and others. The use of social media in large-scale tourism branding activities to attract tourists and improve the nation's economy is usually accompanied by strict management. In addition, support from various stakeholders is needed because it is proven that the government, as a single actor, has limitations in increasing tourism sector revenue through branding.